Strategi Membangun Citra Produk Hello Bubble dalam Komunitas The Crew melalui Brand Ambassador Blackpink - Shanice, Elaine; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
With the presence of technology, it creates very free and broad opportunities for globalization. Freely and widely, other cultures enter and interact with the original culture. One of them is the Korean Wave culture or what is more often called K-Wave. Now the Korean Wave is not just about music, but about the culture of fashion, makeup, drama, food and others. Blackpink itself is a girl group that is known globally thanks to its many achievements in their career. Blackpink is believed to be the brand ambassador for Hello Bubble hair coloring products.